The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/dac.3261
|View full text |Cite
|
Sign up to set email alerts
|

Identifying critical challenges in the adoption of cloud‐based services

Abstract: Summary Cloud computing provides a way to integrate and share information on a real‐time basis across an organization. The current organizations are adopting the cloud services to gain competitive advantage in real‐time data sharing. To meet the current demand in semiconductor industries, they must develop better techniques to produce electronic products at low cost and in a large scale. Adoption of cloud‐based services may resolve the fastest growing demand of technical advancement of semiconductor industries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…11 The main challenging phase comes when deciding the migration methodology such as whether to migrate entirely or partially, 2 to have on-site cloud data center or choose an external service provider, 2 whether to decide on deployment basis or service basis, and whether to share all data or some. 11,19,20,26 Rahi et al 27 have confirmed the "data security" as a challenge in the case of cloud services adoption in semiconductor industries. Most of the legacy systems lack their operability and applicability on the cloud, so it is required to re-engineer the existing systems or adopt the new one.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…11 The main challenging phase comes when deciding the migration methodology such as whether to migrate entirely or partially, 2 to have on-site cloud data center or choose an external service provider, 2 whether to decide on deployment basis or service basis, and whether to share all data or some. 11,19,20,26 Rahi et al 27 have confirmed the "data security" as a challenge in the case of cloud services adoption in semiconductor industries. Most of the legacy systems lack their operability and applicability on the cloud, so it is required to re-engineer the existing systems or adopt the new one.…”
Section: Literature Reviewmentioning
confidence: 97%
“…While adopting cloud PLM, it is very much essential to collaborate all the technical and business enterprise systems to be integrated and interoperable for improved firm's performance. 11,19,20,26 Rahi et al 27 have confirmed the "data security" as a challenge in the case of cloud services adoption in semiconductor industries. Zissis and Lekkas 28 discussed the perception of "perimeter security" among the firms, as the cloud takes the data beyond the organizational perimeter; it creates insecurity and develops distrust.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Liability issues in cloud computing and IoT include ownership of intellectual property, contract terms, and occurrence of undesired situations such as data theft. Specific issues include interruption of information processes that result in downtime and potential financial loss for the users, during system updates and maintenance (Rahi, Bisui and Misra, 2017). Also, non-compliance with the principles of data integrity and protection, as well as negligence of the rights and obligations involved parties can be a liability for the product vendors and users.…”
Section: Main Legal Considerations On Cloud Computing In Kenyamentioning
confidence: 99%
“…Since cloud-based systems in semiconductor industries need Internet connectivity, they are relatively simple to execute. The primary goal of implementing cloud technologies in semiconductor companies is to decrease the complexity of integrated circuit design while also causing efficient performance and lowering costs (Rahi et al , 2017a). Because subscribers' perceptions toward embracing new technologies have such a major effect on the progress of IT implementation (Davis et al ., 1989), it is essential to understand the conditions that influence their perspectives (Li et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%